Trichoderma mediated induced systemic resistance in castor against seedling blight: Trichoderma mediated induced systemic resistance in castor against seedling blight - V DINESH KUMAR; R D PRASAD; K B DURGA BHAVANI; R BHUVANESWARI; VELU MANI SELVARAJ (Journal of Oilseeds Research, 2020)
Colonization of castor roots by Trichoderma induced resistance to seedling blight disease. When compared with untreated seedlings, Phytophthora disease severity was reduced by 93% in Trichoderma (Th4d strain)–treated ones. Induced systemic resistance (ISR) by Trichoderma was confirmed by the expression profiling of a few signature genes known to be up-regulated during ISR.